Is there a transition of solar radiation from dimming to brightening over India? - Soni, V.K.; Pandithurai, G.; Pai, D.S. (Atmospheric research, 2016)
Recent observational studies show that solar radiation incident on ground has not been stable over the last several decades but underwent significant multi-decadal variations. From the 1950s, solar radiation has had a general decreasing trend, named dimming. Since the late 1980s, a trend reversal and partial recovery has been observed at many observations sites across the globe; it is the so-called brightening. The present study examined temporal and spatial trends in surface solar radiation (global and diffuse) and sunshine duration in India using a 40-year data set (1971–2010) of the twelve stations of solar radiation network of the India Meteorological Department. The research work examines the global solar radiation trends in all-sky and cloud-free sky conditions. The long-term variability in the diffuse components of solar radiation, bright sunshine duration, and cloud cover has also been studied over India. India is one of the few regions that showed a continuous and steady decline in global solar radiation from the 1970s to 2000. The declining trend of all-sky global irradiance over India as a whole was 0.6Wm−2 year−1 during 1971–2000 and 0.2Wm−2 year−1 during 2001–2010. A third-order polynomial fit to the data indicated a reversal in all-sky global irradiance around 2001 at some sites. Reversal or stabilization of global irradiance is also seen in seasonal mean values at some of the stations. The reversal in clear-sky global irradiance was clearly evident from 2001. Similar trend is also observed in bright sunshine duration. This confirms the well-known phenomenon of global dimming and global brightening over India. The analysis of global irradiance data highlights the fact that in general the dimming/brightening is station dependent because of regional sources and meteorology which contribute to the variation in solar irradiance. •We examine long-term trends in global and diffuse irradiance during 1971–2010.•Many sites in India show stabilization or increase of global irradiance.•Clear-sky global irradiance averaged over India shows reversal from 2001.•Similar trend is also observed in bright sunshine duration.•The result confirms the phenomenon of global dimming and brightening over India.